Transcriptome-wide identification of differentially expressed genes in Procambarus clarkii in response to chromium challenge. Issue 87 (April 2019) - Meng, Xun; Hong, Liang; Yang, Ting-Ting; Liu, Yu; Jiao, Ting; Chu, Xiao-Hua; Zhang, Dai-Zhen; Wang, Jia-Lian; Tang, Bo-Ping; Liu, Qiu-Ning; Zhang, Wei-Wei; He, Wen-Fei
Abstract: Because of the high protein content and rich meat quality of crayfish Procambarus clarkii, it has become widely popular in China in recent years and has a high economic value. When P. clarkii is stimulated by heavy metals, it reacts to oxidation. P. clarkii has evolved antioxidant defense systems, including antioxidant enzymes such as catalase (CAT). The hexavalent form of Cr (VI) is a pathogenic factor that is of particular concern in aqueous systems because of its great toxicity to living organisms. In this study, we characterized the transcriptome of P. clarkii using a RNA sequencing method and performed a comparison between K2 Cr2 O7 -treated samples and controls. In total, 34, 237 unigenes were annotated. We identified 5098 significantly differentially expressed genes (DEGs), including 2536 and 2562 were significantly up-regulated and down-regulated, respectively. In addition, quantitative real time-PCR (qRT-PCR) confirmed the up-regulation of a random selection of DEGs. Our results contribute to a more comprehensive understanding of the antioxidant defense system used by P. clarkii in response to heavy metal stress. Highlights: The chromium-stimulated hepatopancreas transcriptome of Procambarus clarkii was constructed. Totally 34, 237 unigenes was annotated from the transcriptome. Totally 5098 DGEs were identified including 2536 up- and 2562 down-regulated unigenes.